IDENTIFICATION OF POSSIBLE INHIBITORS OF CORONAVIRUS HEMAGGLUTININ-ESTERASE THROUGH MOLECULAR DOCKING, MOLECULAR DYNAMICS SIMULATION AND BINDING FREE ENERGY CALCULATION - BHATI, NEHA; CHAUDHARY, ANAMIKA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Vaccines are urgently needed to control the 2019 novel coronavirus disease (COVID-19) and help restore normal conditions before the pandemic. The hemagglutinin-esterase belongs to viral envelope glycoproteins family that facilitates reversible binding to O-acetylated sialic acids as a result of acting as lectins as well as receptor-destroying enzymes. Associated hemagglutinin-esterase take place in influenza C, toro-, besides coronaviruses. At this point, we initiate the crystal assembly of a coronavirus hemagglutinin-esterase in composite with its receptor through RCSB-PDB (id 5n11). We prepared this protein for docking more inhibitors with Autodock 4.0 by adding polar hydrogen and Kollman charges. We described its active site through Dog Site Scorer server and found Bovine corona virus is very near to our target protein with the help of phylogenetic analysis through MEGA-X software and proposed that we can do drug designing on Bovine coronavirus too for clinical trial on animal.